Metagenomic next-generation sequencing for Mycobacterium tuberculosis complex detection: a meta-analysis - Li, Yulian; Bian, Wentao; Wu, Shiping; Zhang, Jie; Li, Dan (Frontiers in Public Health, 2023)
Objective Metagenomic next-generation sequencing (mNGS) has been gradually applied to the diagnosis of tuberculosis (TB) due to its rapid and highly sensitive characteristics. Despite numerous studies on this subject, their results vary significantly. Thus, the current meta-analysis was performed to assess the performance of the mNGS on tuberculosis. Methods PubMed, Embase, Web of Science, and The Cochrane Library were searched up to June 21, 2023. Studies utilizing the mNGS for tuberculosis detection were included. The risk of bias was assessed by QUADAS-2, and a meta-analysis was performed with STATA14.0 software. Results Seventeen studies comprising 3,205 specimens were included. The combined sensitivity and specificity of mNGS for clinical specimens were 0.69[0.58–0.79] and 1.00[0.99–1.00], respectively. Subgroup analysis identified sequencing platform, diagnostic criteria, study type, sample size, and sample types as potential sources of heterogeneity. Cerebrospinal Fluid (CSF) has a lower sensitivity of 0.58 (0.39–0.75). In a population with a 10% prevalence rate, the accuracy of sensitivity reached 94%. Conclusion Metagenomic next-generation sequencing technology exhibits high sensitivity and speed in diagnosing Mycobacterium tuberculosis. Its application in mono and mixed infections peoples shows promise, and mNGS is likely to be increasingly used to address challenges posed by Mycobacterium tuberculosis complexes in the future.